Um estudo longitudinal sobre as hipersegmentações de palavras escritas nos anos finais do ensino fundamental - Silva, Lilian Maria da [UNESP] (2014)
In this paper, we analyze the calls hypersegmentation of words that relate to when, within a word, it identifies space of written not predicted by orthography (e.g. da quela and morava, when at the limits convention are daquela and morava). Through a longitudinal study of written texts of the last four years of Elementary School, we develop a general description of the data and the trajectory of each of the written investigated, with the aim of: (i) to describe the distribution of the analyzed occurrences through the school years of Elementary School and written and to identify possible linguistic regularities of these non-conventional spellings of words that characterize the end of key stage of schooling, and (ii) to interpret the events that did not meet the more general regularities, but which were relevant in the understanding of a more particular subject with (his/her) writing. Depending on the object of investigation, we base ourselves in theoretical discussions about the boundaries unconventional words (ABAURRE, 1991c; TENANI, 2010, CUNHA, 2004), the notion of word (SCHWINDT, 2001; BISOL, 2005; SIMIONI, 2008) and the writing constitution (CORRÊA, 2004). The results of the paper related to the first objective, indicated that: (i) occurrences of hypersegmentation decreased through the school years; (ii) most written concluded Elementary School producing hypersegmentation, although hypersegmentation number has decreased compared to the type of word that was hipersegmented and extension (given by the number of words) of written texts; (iii) the words that remained to be hypersegmented were those ones that allowed the relation between unstressed syllables and possible grammatical classes and between sequences that could be interpreted as being verb + enclitic pronoun (according to the Portuguese grammar), and (iv) prosodic nature information and retrievable linguistic information about inserting the written in literacy/writings ...